PENGALAMAN POLA ASUH PADA IBU DENGAN ANAK YANG MENGALAMI STUNTING DI KOTA AMBON - Kadatua, Marwa Hasan; Wildia Nanlohy; Melawati Wakano; Angelica Girlani Yesualdus (Institut Citra Internasional, 2026)
Stunting is a serious global health problem and is a major challenge in efforts to improve child welfare throughout the world, especially indeveloping countries like Indonesia. In Maluku, stunting cases are increasing, especially in the working area of the Belakang Soya Health Center,Ambon City, stunting cases continue to increase every year. This study aims to determine theexperiencesof mothers in the first 1000 days of achild's life faced when children experiencing stunting. Research objectives : Experience of mother's parenting patterns in the first 1000 days of achild's life when children experiencing stunting by looking at maternal nutrition during pregnancy, exclusive breastfeeding, and feeding practices (MP-ASI) in the working area of the Belakang Soya Health Center, Ambon City. Research Methods : The type of research used is qualitative research with a phenomenological approach. Informants were 10 mothers with children with stunting. This study was conducted from September to November 2024. Results : The results of this study indicate that there are 3 dimensions studied, namely the experience of the first 1000 days of a child's life including maternal nutrition during pregnancy, it was found that some mothers had poor eating patterns during pregnancy, did not provide exclusive breastfeeding, and provided non-nutritious food in feeding practices (MP-ASI). Conclusion : The role of mothers during the first 1000 days of a child's life is very important, especially in fulfilling nutrition during pregnancy, providing exclusive breastfeeding, andappropriate MP-ASI.